Navigating learning spaces: a comparative exploration of hard-of-hearing students experience in traditional face-to-face and online classrooms - Muhammad, Siti Salmiah; Sheikh Ahmad, Ismail; Hashim, Sulaiman (Zes Rokman Resources, 2024)
This paper presents a comparative exploration of the experiences of hard-of-hearing students in traditional and online classrooms within the context of higher education in Malaysia. As educational institutions increasingly adopt online learning environments, understanding how students with hearing impairments navigate these changes is crucial for promoting inclusive education. Based on a case study approach, the study involves eight hard-of-hearing students from selected Malaysian universities. Data were collected through semi-structured interviews and self-journal writing. The research explores key themes such as communication accessibility, social interaction and peer communication, instructor interaction and support, classroom environment, distractions, and visuals and learning materials employed. Findings reveal that online classrooms, particularly asynchronous design, offer flexibility and access to multimedia resources; they also present significant challenges, such as unreliable captioning and limited real-time interaction. In contrast, traditional classrooms provide opportunities for immediate communication and face-to-face support but often need more adequate accommodations. The study highlights the need for more consistent and effective accommodations across both learning environments to ensure equitable access to education for hard-of-hearing students. Practical recommendations include improving the quality and availability of captioning and embedding sign language and interpretation, enhancing training for instructors on inclusive teaching strategies, and exploring hybrid learning and flipped classroom models that combine the benefits of both online and traditional formats. This research contributes to a deeper understanding of how different educational settings impact the academic experiences of hard-of-hearing students. It provides valuable insights for improving accessibility for students with hearing impairment in Malaysian higher education.